The Feasibility of Coffee Industries in West Kalimantan Province - Rudy Setyo Utomo (Jurnal Bina Praja, 2014)
The purpose of this study was to determine the feasibility of the coffee industry folk as a commercial producer in West Kalimantan. Research conducted descriptive and observation to determine the potential of raw materials, market potential and marketing, availability of technology, and financial feasibility analyzes plant establishment. The results of the study showed that the availability of raw materials such as coffee yields declined every year and its availability on every small community, and not attractive to farmers for commercial cultivation, where plants cannot compete with rubber, palm oil, or other horticultural crops or plantation, so people are reluctant to plant coffee again. Although, the marketing of coffee available on the domestic market, national market and abroad, but the quality of the coffee that is associated with superior taste, aroma, and geography indications is its own advantages, which have not seemed to result from West Kalimantan coffee. Coffee processing technology indicates the readiness of technology for applications, such as the technology to produce coffee of primary and secondary copy. Advice can be given is the cultivation of coffee and wild civet coffee products (Paradoxurus hermaphrodites) from Sambas district and fostered intensive note by the local government, in order to have a competitive commercialization opportunities. Local Government should re-establish cultivation techniques and management of coffee farming.